2018
DOI: 10.1155/2018/7647562
|View full text |Cite
|
Sign up to set email alerts
|

Assessing User Transparency with Muscle Synergies during Exoskeleton-Assisted Movements: A Pilot Study on the LIGHTarm Device for Neurorehabilitation

Abstract: Exoskeleton devices for upper limb neurorehabilitation are one of the most exploited solutions for the recovery of lost motor functions. By providing weight support, passively compensated exoskeletons allow patients to experience upper limb training. Transparency is a desirable feature of exoskeletons that describes how the device alters free movements or interferes with spontaneous muscle patterns. A pilot study on healthy subjects was conducted to evaluate the feasibility of assessing transparency in the fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…In the context of promoting rehabilitation, designing robots and assessing their effects in a context of motion variability may enhance their efficacy, as well as matching the assessment of variability with muscle synergies. Following these premises, the evaluation of robot-assisted training seems a natural match with the muscle synergies framework, and in fact preliminary works have exploited this concept, assessing human-robot interaction with muscle synergies (Tropea et al, 2013; Coscia et al, 2014; Lunardini et al, 2016; Pirondini et al, 2016; Chiavenna et al, 2018; di Luzio et al, 2018; Scano et al, 2018). The database here presented, properly expanded and matched with patients, could be a milestone reference point for designing training paradigms or provide in depth evaluations, extending the results found in previous works (d’Avella et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of promoting rehabilitation, designing robots and assessing their effects in a context of motion variability may enhance their efficacy, as well as matching the assessment of variability with muscle synergies. Following these premises, the evaluation of robot-assisted training seems a natural match with the muscle synergies framework, and in fact preliminary works have exploited this concept, assessing human-robot interaction with muscle synergies (Tropea et al, 2013; Coscia et al, 2014; Lunardini et al, 2016; Pirondini et al, 2016; Chiavenna et al, 2018; di Luzio et al, 2018; Scano et al, 2018). The database here presented, properly expanded and matched with patients, could be a milestone reference point for designing training paradigms or provide in depth evaluations, extending the results found in previous works (d’Avella et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of how the presence of the device acting with the limb might alter synergies. The effect of wearable robotic devices on muscle synergies has been studied in multiple circumstances, including point-to-point arm reaching movements moving freely versus moving inside an exoskeleton [8] and for activities of daily living performed inside versus outside an exoskeleton [9]. All results indicate that the shape of the muscle synergy vectors was preserved across conditions; only the activations of the synergies were changed.…”
Section: Introductionmentioning
confidence: 99%
“…One such study on a limited sample of patients concluded that the treatment prompted patients to modify the coordinated activity of muscle groups, though the reorganization of the rules underlying motor control was characterized by a significant inter-patient variability (Tropea et al, 2013 ). Other studies discussed the use of muscle synergies and provided detailed accounts of interactions with rehabilitation devices (Coscia et al, 2014 ; Pirondini et al, 2016 ; Chiavenna et al, 2018 ), but their analyses only concerned healthy people.…”
Section: Introductionmentioning
confidence: 99%